ANALISIS CONTINUOUS IMPROVEMENT PADA BUDAYA MUTU MADRASAH DI KABUPATEN BANYUWANGI - Fauzi, Muhammad Irfan; Aimah, Siti; Imam Khaudli, Muhammad (UIN Sumatera Utara Medan, 2024)
Management of learning values, as is known as TQM, is a procedure for continuously strengthening performance at every level of operation or process in every functional zone in a particular organization with a broad background, namely the use of human resources and a lot of existing capital. Meanwhile,